2021
DOI: 10.1021/acsphotonics.1c00808
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Molecular Optomechanics with Hybrid Dielectric–Metallic Resonators

Abstract: Molecular optomechanics describes surface-enhanced Raman scattering using the formalism of cavity optomechanics as a parametric coupling of the molecule’s vibrational modes to the plasmonic resonance. Most of the predicted applications require intense electric field hotspots but spectrally narrow resonances, out of reach of standard plasmonic resonances. The Fano lineshapes resulting from the hybridization of dielectric–plasmonic resonators with a broad-band plasmon and narrow-band cavity mode allow reaching s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 62 publications
(131 reference statements)
0
15
0
Order By: Relevance
“…Because of the large decay rate of plasmonic resonances, the electromagnetic enhancement offered in SERS is intrinsically broad, limiting the coherence of the optomechanical interaction. While the low-quality factors (Q) of plasmonics mean that sideband-resolved plasmonic SERS is out of reach, recent work has argued that sideband-resolved SERS is possible via the use of a hybrid plasmonic-photonic resonator, both theoretically (15,16) and experimentally (17). A hybrid resonator combines a high-Q photonic resonator with a low mode volume plasmonic resonance (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the large decay rate of plasmonic resonances, the electromagnetic enhancement offered in SERS is intrinsically broad, limiting the coherence of the optomechanical interaction. While the low-quality factors (Q) of plasmonics mean that sideband-resolved plasmonic SERS is out of reach, recent work has argued that sideband-resolved SERS is possible via the use of a hybrid plasmonic-photonic resonator, both theoretically (15,16) and experimentally (17). A hybrid resonator combines a high-Q photonic resonator with a low mode volume plasmonic resonance (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…A hybrid resonator combines a high-Q photonic resonator with a low mode volume plasmonic resonance (18)(19)(20)(21). The resulting resonances are narrower than the usual molecular vibrational resonance frequencies, allowing for sideband-resolved SERS with single optical resonators and strong SERS enhancements (16,22).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in response to surprising experimental results [1,2], it has been shown that Raman scattering of light from molecules in plasmonic cavities can be cast as an optomechanical process [3][4][5][6][7][8], with molecular vibrational modes playing the role of ultra-high frequency mechanical resonators. This realization has brought the extensive set of tools developed for conventional cavity optomechanics to the field of surface-or tip-enhanced Raman scattering (SERS and TERS) research [9][10][11][12].…”
mentioning
confidence: 99%
“…This realization has brought the extensive set of tools developed for conventional cavity optomechanics to the field of surface-or tip-enhanced Raman scattering (SERS and TERS) research [9][10][11][12]. The resulting formalism of molecular optomechanics has led to new insights into the correlations of inelastically-scattered Raman light [4,13], extension of the quantum-mechanical description of single-and multi-mode plasmonic cavities [5,6,14,15], and the dynamics of systems with multiple molecules [16]. It has also enabled theoretical proposals [17], and experimental demonstrations of new THz detection techniques [18,19].…”
mentioning
confidence: 99%
“…Recently, a molecular optomechanics theory has been proposed to account for the dynamical nature of the plasmon-vibration interaction inside a plasmonic nanocavity, , in alignment with the well-established coupling between cavity photon and mechanical oscillation . The theory of molecular optomechanics has significantly advanced in the past few years, providing quantum mechanical interpretation to the nonlinear response of the SERS signal as laser power is increased. The nonlinear effect has been verified experimentally for molecules and inorganic crystals in plasmonic nanocavities.…”
mentioning
confidence: 99%